PENINGKATAN KUALITAS TANAH DALAM MEWUJUDKAN PRODUKTIVITAS LAHAN PERTANIAN SECARA BERKELANJUTAN - Adnyana, I Made (Bumi Lestari Journal of Environment; Vol 11 No 1 (2011), 2011)
Soil survey and analysis for evaluating soil quality was done at paddy soil of Tabanan regency, to rehabilitate the soil quality on physically, chemically, and biologically, respectively, and for increased the sustainable productivity. Soil samples were collected from top soil (0-20 cm) and subsoil (20-60 cm), selected on composite sampling. In this study, the soil characteristics analyzed is: soil texture, caution exchange capacity, base saturated, organic matter, P and K contents. Analysis results showed that most of Tabanan regency paddy soil had a medium physical-quality, very low to low chemical-quality, low biological-quality, and low productivity. To implementation the land agriculture productivity, could be increased the soil quality with integrated fertilization recommendation by combined inorganic fertilizers (Urea and SP-36) and organic fertilizers (manure and straw) with suitable dosage.
Keywords: soil quality, agriculture productivity, soil characteristics, sustainable